Sustainable affordable housing in Sarawak - 432429 Ng, Khin Howe; Mohd. Hamdan Ahmad, supervisor; Fakulti Alam Bina (2008)
Project Paper (Sarjana Muda (Senibina)) - Universiti Teknologi Malaysia, 2008